2010
DOI: 10.1111/j.1600-0447.2010.01635.x
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter volume deficits and correlation with insight and negative symptoms in first-psychotic-episode subjects

Abstract: Our findings support an association between prefrontal, temporal, and cerebellar deficits and lack of insight in schizophrenia and confirm previous findings of GM deficits in patients since the first episode of psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 74 publications
7
52
0
1
Order By: Relevance
“…70,71 The specific rIFG volume loss observed here may also contribute to the differential clinical profiles of these cross-disorder subtypes, as the ED patients demonstrate greater symptom severity across all domains of positive, negative and general symptoms and poorer global functioning. Previous studies have found associations between rIFG volume and severity of both positive [72][73][74] and negative symptoms, 75 while a recent meta-analysis also identified that rIFG volume may differentiate high-risk individuals who transition to psychosis from those who do not transition. 76 Notably, an association has been reported between increasing age and reduced volume of the rIFG and superior temporal gyrus in a subsample of patients with schizophrenia who have prominent symptoms of paranoia.…”
Section: J Psychiatry Neurosci 2015;40(1)mentioning
confidence: 99%
“…70,71 The specific rIFG volume loss observed here may also contribute to the differential clinical profiles of these cross-disorder subtypes, as the ED patients demonstrate greater symptom severity across all domains of positive, negative and general symptoms and poorer global functioning. Previous studies have found associations between rIFG volume and severity of both positive [72][73][74] and negative symptoms, 75 while a recent meta-analysis also identified that rIFG volume may differentiate high-risk individuals who transition to psychosis from those who do not transition. 76 Notably, an association has been reported between increasing age and reduced volume of the rIFG and superior temporal gyrus in a subsample of patients with schizophrenia who have prominent symptoms of paranoia.…”
Section: J Psychiatry Neurosci 2015;40(1)mentioning
confidence: 99%
“…5,6 Others reported less grey matter tissue confined to the frontal and temporal cortex in patients with first-episode psychosis. 7,8 Contradictory data, such as a greater grey matter tissue in the frontal and temporal lobes in patients with first-episode psych osis have also been reported. 9 The region of interest (ROI) analyses in such patients documented lower volume in the superior temporal gyrus, 10 insula, 11 cingulate cortex 12 and at least 1 subdivision of the frontal lobe.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, gray matter reduction in the cerebellum, prefrontal and temporal regions was reported in firstepisode psychosis and associated with impaired insight 114 .…”
Section: Abnormalities In Brain Function As a Root Of Poor Insightmentioning
confidence: 99%